The Tradition of Reading Surah Yasin and Surah Al-Kahf in Daar Al-Muttaqin Islamic Boarding School, Klaten, Central Java - Rofi' Irhas Putratama (Indonesia); Riyani (Turki) (Mafatih, 2023)
This research reveals that the tradition of reading (reciting) Surah Yasin and Surah Al-Kahf in the Daar Al-Muttaqin Islamic Boarding School is one of the various phenomena of Islamic anthropology. Researchers try to link the scientific study of the Qur'an and interpretation with the scientific discipline of anthropology. The focus of this research is how the traditions that the author mentioned earlier are studied using anthropological and phenomenological approaches. Researchers are trying to uncover what has become a tradition at the Daar Al-Muttaqin Islamic boarding school, especially in reciting surah Yasin and surah al-Kahf. This research is qualitative and the researchers used the interview method to collect existing data sources in the field. In the interview process that was conducted, the researcher found that the reading tradition is a mantra from the caretaker or manager of the cottage on the virtues that exist in surah Yasin and surah al-Kahf. This is what the researcher will later study further about the virtues that exist in surah Yasin and surah al-Kahf with the disciplines of the Qur'an and interpretation and relate them to the phenomenon of the tradition of reciting these surahs using anthropological disciplines.